THE RELATIONSHIP BETWEEN LIFESTYLE AND THE INCIDENCE OF HYPERTENSION IN THE COMMUNITY IN THE WORKING AREA OF THE LAGEUN COMMUNITY HEALTH CENTER, SETIA BAKTI SUB-DISTRICT, ACEH JAYA DISTRICT IN 2024 - Balqis, Putri (Transpublika Publisher, 2024)
High blood pressure or hypertension is an increase in diastolic pressure of more than 90 mmHg and systolic pressure of more than 140 mmHg. This disease is usually not accompanied by symptoms (asymptomatic). According to JNC hypertension occurs when blood pressure is more than 140/90 mmHg. Based on the data input into SPSS, it is related to age and physical activity and age to eating restrictions. Based on the research results, the total number of respondents aged with physical activity was 84 people, with 9 people who were sedentary with 100%, and the total respondents aged with smoking were a total of 13 people and those who did not smoke were 80 people with a total of 93 respondents with 100%. and those aged with abstinence eating with a total of 84 respondents who abstain from eating, and 9 who do not abstain from eating with a total of 93 respondents with 100%.